2016
DOI: 10.1128/jvi.00509-16
|View full text |Cite
|
Sign up to set email alerts
|

Trimer Enhancement Mutation Effects on HIV-1 Matrix Protein Binding Activities

Abstract: The HIV-1 matrix (MA) protein is the amino-terminal domain of the HIV-1 precursor Gag (Pr55Gag) protein. MA binds to membranes and RNAs, helps transport Pr55Gag proteins to virus assembly sites at the plasma membranes of infected cells, and facilitates the incorporation of HIV-1 envelope (Env) proteins into virions by virtue of an interaction with the Env protein cytoplasmic tails (CTs). MA has been shown to crystallize as a trimer and to organize on membranes in hexamer lattices. MA mutations that localize to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 56 publications
6
43
0
Order By: Relevance
“…The W666A and I675A mutations diminished the infectivity of cell-free virions, whereas previous studies have shown that membrane fusion mediated by these Env mutants expressed at the cell surface in the absence of other viral proteins is not affected (52). It may be that the MPER mutations adversely affect Env function in the context of assembled cell-free virions, where interactions between MA and the CT of gp41 (61)(62)(63) can modulate the structure and function of the ectodomain (64 -66). To investigate the influence of the CT on the function of the MPER mutants, stop codons were introduced after positions 712, 727, and 752 in the WT, W666A, and I675A pcDNA3.1-AD8env expression vectors to give the ⌬CT144, ⌬CT129, ⌬CT104 mutants, respectively (Fig.…”
Section: Mutations In the Ct Of Gp41 Mitigate The Cell-free Virus Infmentioning
confidence: 84%
See 1 more Smart Citation
“…The W666A and I675A mutations diminished the infectivity of cell-free virions, whereas previous studies have shown that membrane fusion mediated by these Env mutants expressed at the cell surface in the absence of other viral proteins is not affected (52). It may be that the MPER mutations adversely affect Env function in the context of assembled cell-free virions, where interactions between MA and the CT of gp41 (61)(62)(63) can modulate the structure and function of the ectodomain (64 -66). To investigate the influence of the CT on the function of the MPER mutants, stop codons were introduced after positions 712, 727, and 752 in the WT, W666A, and I675A pcDNA3.1-AD8env expression vectors to give the ⌬CT144, ⌬CT129, ⌬CT104 mutants, respectively (Fig.…”
Section: Mutations In the Ct Of Gp41 Mitigate The Cell-free Virus Infmentioning
confidence: 84%
“…Several lines of evidence indicate that the gp41 CT interacts with the MA protein shell beneath the inner leaflet of the viral envelope. In this context, the MA shell may include a hexameric array of MA trimers, the central aperture of the hexamer potentially providing a docking site for the CT (61)(62)(63)84). Mutations in MA such as L49D can destabilize the interaction between gp120 and gp41 on the virion surface; however, Env can be uncoupled from the L49D MA defect by ⌬CT144, and this effect can be reproduced by the Y712S substitution in the…”
Section: Mutations In the Ct Of Gp41 Mitigate The Cell-free Virus Infmentioning
confidence: 99%
“…Eric Barklis (Oregon Health and Science University) discussed a long-standing question in the field—does Env directly bind MA, and if so, why are so few Env trimers packaged onto HIV-1 particles? To address these questions, Barklis found that the 62QR HIV-1 MA mutant, reported by the Freed lab to rescue Env incorporation defects [ 18 ], forms trimers more efficiently than WT MA in a UV-crosslinking assay, and is bound more efficiently than WT MA to GST-coupled gp41 CT [ 32 ]. The presence of RNA reduced binding between MA and the gp41 CT, perhaps by diminishing MA trimerization, and inositol hexakisphosphate (IP 6 ) increased MA binding to the gp41 CT, perhaps by increasing the MA trimerization.…”
Section: Structurementioning
confidence: 99%
“…Incubation products were fractionated on 12% SDS-PAGE gels under reducing conditions (278) in parallel with molecular weight size standards, and immunoblotted for MA detection as described previously (278), using a primary mouse monoclonal antibody to MA (Capricorn #01848170) at a 1:2000 dilution, an alkaline phosphatase-conjugated anti-mouse secondary antibody (Promega #S3728) at a 1:15,000 dilution, and nitro-blue tetrazolium (NBT; Promega) plus 5-bromo-4-chloro-3'-indolyphosphate (BCIP; Promega) for visualization (278). Blots were scanned on and Epson Perfection 1240U scanner, band intensities were obtained with Image J software, and percentage crosslinking levels were determined from dimer divided by dimer plus monomer MA band intensities.…”
Section: Methodsmentioning
confidence: 99%